Conjuntura política brasileira em 1968 : o real e o imaginário na narrativa jornalística de O Globo - Müller, Luana Chinazzo (2019)
In the year that this research was developed, Institutional Act n. 5 (AI-5), which started difficult years, marked by police repression, censorship, persecution and torture of opponents, was 50 years old, and, throughout that time, the communication vehicles have changed their position a lot, changing the imaginary of the period and the role they played. The present research starts from two question questions: 1) How the newspaper O Globo narrated the main political events that preceded the AI-5 in 1968? 2) What layers of real and imaginary are we able to uncover in the analyzed journalistic narrative? Through the narratives of the lived, method proposed by Silva (2003), we analyze the journalistic narrative, seeking to unveil the imaginary hidden in the newspaper. The research is theoretically supported by bibliographies of the military dictatorship in Brazil, the Brazilian press and the relationship between both. We also deepen notions such as narrative, event and imaginary. As main result, we could understand the narrative construction of the political conjuncture of 1968, with its episodes and characters, in the pages of O Globo, and we uncovered the imaginary layers that permeate the discourse.